KONSTRUKSI HAK MENGUASAI NEGARA DALAM TATA LAKSANA PENGADAAN TANAH BAGI KEPENTINGAN UMUM DI KABUPATEN SEMARANG - Sumral Buru Manoe (Jurnal Pembaharuan Hukum, 2014)
In the implementation of land acquisition for public purposes (project Semarang-Solo toll road) there has been a priority of the State's Rights. implementation of the State's rights to land are not always parallel with the ideals of prosperity, welfare and even justice. The phenomenon of the right to control the state, namely the practice of takeover of the land belongs to the people in the name of public interest and or preferential right to control the country and even a common trigger factor land conflict. In the development of the law is not only focused on textuality laws alone but must also pay attention to the interests of the community that continues to grow, especially related to land issues. This study uses socio-legal research approach, meaning that not only reviewing an issue of legislation but also the reality that occurs in the community related to the problems discussed. the results obtained to mention that the process of land acquisition for the construction of the Semarang-Solo toll road in accordance with procedures applicable law, namely to put the negotiation process (consensus), especially about the amount of compensation awarded. However, a strong indication of consensus is not performed substantially, only meets the provisions of the Act alone.